Empowerment, intimate partner violence and skilled birth attendance among women in rural Uganda - Kwagala, Betty; Nankinga, Olivia; Ojiambo Wandera, Stephen; Ndugga, Patricia; Kabagenyi, Allen (Reproductive health, 2016)
There is limited research on how the empowerment of women and intimate partner violence (IPV) are associated with skilled birth attendance (SBA) among rural women in Uganda. Therefore, the aim of this paper was to investigate the association between women’s empowerment, their experience of IPV and SBA in rural Uganda. Methods: Using data from the Uganda Demographic and Health Survey (UDHS), we selected 857 rural women who were in union, had given birth in the last 5 years preceding the survey and were selected for the domestic violence (DV) module. Frequency distributions were used to describe the background characteristics of the women and their partners. Pearson’s chi-squared (χ2) tests were used to investigate the associations between SBA and women’s empowerment; and partners’ and women’s socio-demographic factors including sexual violence. Multivariable logistic regression analyses were used to examine the association between SBA and explanatory variables. Results: More than half (55 %) of the women delivered under the supervision of skilled birth attendant. Women’s empowerment with respect to participation in household decision-making, property (land and house) (co)ownership, IPV, and sexual empowerment did not positively predict SBA among rural women in Uganda. Key predictors of SBA were household wealth status, partners’ education, ANC attendance and parity. Conclusions: For enhancement of SBA in rural areas, there is a need to encourage a more comprehensive ANC attendance irrespective of number of children a woman has; and design interventions to enhance household wealth and promote men’s education.
Keywords: Empowerment; Intimate Partner Violence; Skilled Birth Attendance; Rural; Africa